2022
DOI: 10.3389/fnagi.2022.874734
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Real-Time Quaking-Induced Conversion for the Diagnosis of Human Prion Diseases

Abstract: Prion diseases are rapidly progressive, invariably fatal, transmissible neurodegenerative disorders associated with the accumulation of the amyloidogenic form of the prion protein in the central nervous system (CNS). In humans, prion diseases are highly heterogeneous both clinically and neuropathologically. Prion diseases are challenging to diagnose as many other neurologic disorders share the same symptoms, especially at clinical onset. Definitive diagnosis requires brain autopsy to identify the accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…(5) Quaking induces fragmentation of the PrP Sc fibrils. (6) The process is repeated [ 83 , 91 , 92 ]. (B) Aggregation of recPrP C in RT-QuIC was assessed in the CSF from twelve different CJD patients.…”
Section: Resultsmentioning
confidence: 99%
“…(5) Quaking induces fragmentation of the PrP Sc fibrils. (6) The process is repeated [ 83 , 91 , 92 ]. (B) Aggregation of recPrP C in RT-QuIC was assessed in the CSF from twelve different CJD patients.…”
Section: Resultsmentioning
confidence: 99%
“…reviewing the effect of different recombinant prion protein substrates on VV1 and MM2C identified similar findings. Interestingly they also found that there was increased sensitivity in the improved QuIC (IQ-CSF) compared to the prior protocol QuIC (PQ-CSF) in those with MM2C (70% vs 40%) but this was found not to be the case in those with VV1 [ 25 , 26 ]. The reduced PrP sc seeding efficiency in these subtypes may correlate with the atypically long durations when compared to the other variants of sporadic CJD with a median duration of 3–5 months.…”
Section: Discussionmentioning
confidence: 99%
“…As with prions and other amyloid forms of proteins [98,107], that are often highly resistant to proteolysis (e.g. [108,109]), the existence of these ‘fibrinaloid’ microclots implies their comparative resistance to normal fibrinolysis [110,111], with their precise structures [112] being affected by other small and macromolecules and ions that they may have bound [97,103,113-119]. The varieties of stable macrostates into which a given amyloidogenic sequence can fold (even under the same conditions [120,121]) are referred to as different ‘strains’ [122-132] or ‘polymorphisms’ [133-144], and in some cases are sufficiently stable (i.e.…”
Section: Introductionmentioning
confidence: 99%